Codigestão anaeróbia de biomassa de microalgas e esgoto sanitário em reator UASB - Maciel, Gabriela Boechat Povoa (2019)
This study aims to evaluate the effect of combined municipal wastewater with microalgae biomass anaerobic co-digestion on an Upflow Anaerobic Sludge Blanket (UASB) reactor through the performance analysis during 416 days. The present contribution aims to study municipal wastewater combined with microalgae biomass anaerobic co-digestion effect on an Upflow Anaerobic Sludge Blanket (UASB) reactor through the performance analysis during 416 days. The UASB used has 3.78 m³ of usable volume and is 4.8 m high. Furthermore, the reactor operated on 25oC temperature and presented average hydraulic detention time and VOC content equal to 9.0 hours and 1.06 kgCOD.m-3.d-1. The effluent presented average COD of 338mgL 1 , BOD5/COD of 0.63, TSS 350mg.L-1 and VSS of 300mgL-1. Moreover, microalgae biomass introduced in the UASB reactor presented VS/TS relation equal to 0.60. The sludge profile from UASB revealed that the process responded to microalgae insertion and their accumulation in the digestion compartment. In addition, the mass balance, based on cells counting, showed that UASB does not expel microalgae. Further, the microalgae distribution is majorly concentrated between 0.16 and 1.29m (30.5% of the cells) and 1.29 and 2.29m (20.3% of the cells). On the other hand, 36.7% of microalgae and municipal wastewater COD was converted to sludge. Scanning electron microscopy showed the presence of not lysed microalgae cells in all UASB effluent samples, which highlights the need for hydrolysis to increase biomass biodegradability in co-digestion 1 process. This phenomenon is due to a 0.49m³.d (0,1Nm³CH4.KgCODremoved-1) average biogas production, which is smaller than the obtained in the operation of the same methanogenic reactor of microalgae collected after coagulation with TANFLOC and sedimentation, before and after the alkaline hydrolysis to solubilize the COD. At last, a negative effect of TANFLOC coagulant over methane production with UASB sludge even after submission to alkaline hydrolysis.